Relating QRS voltages to left ventricular mass and body composition in elite endurance athletes - De Bosscher, R.; Moeyersons, J.; Dausin, C.; Claeys, M.; Janssens, K.; Claus, P.; Goetschalckx, K.; Bogaert, J.; Van De Heyning, C. M.; Paelinck, B.; Sanders, P.; Kalman, J.; et al. (European Journal of Applied Physiology, 2023)
Purpose Electrocardiogram (ECG) QRS voltages correlate poorly with left ventricular mass (LVM). Body composition explains some of the QRS voltage variability. The relation between QRS voltages, LVM and body composition in endurance athletes is unknown.